2005
DOI: 10.1111/j.1600-0501.2005.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of image‐guided implantology

Abstract: Image-guided insertion of dental implants is significantly more accurate than manual insertion. However, the accuracy that can be achieved with manual implantation is sufficient for most clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 24 publications
(31 reference statements)
7
137
2
2
Order By: Relevance
“…In an experiment by Sarment et al using the Simplant system, it was reported that the angle deviation was 4.5±2.0° and the position deviations were 0.9±0.5 mm at the top of the implant body and 1.0±0.6 mm at the bottom of the implant body 11) . In another study by Brief et al using the IGI system, it was reported that angle deviation was 4.21° and position deviations were 0.65 mm at the top of the implant body and 0.68 mm at the bottom of the implant body 12) . Using the IGI system too in their study, Casap et al reported that the position deviation 0.35±0.14 mm 13) .…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment by Sarment et al using the Simplant system, it was reported that the angle deviation was 4.5±2.0° and the position deviations were 0.9±0.5 mm at the top of the implant body and 1.0±0.6 mm at the bottom of the implant body 11) . In another study by Brief et al using the IGI system, it was reported that angle deviation was 4.21° and position deviations were 0.65 mm at the top of the implant body and 0.68 mm at the bottom of the implant body 12) . Using the IGI system too in their study, Casap et al reported that the position deviation 0.35±0.14 mm 13) .…”
Section: Discussionmentioning
confidence: 99%
“…In oral and cranio-maxillofacial surgery, registration is often performed using intraoral fiducial markers mounted on an intraoral dental splint device [16,21]. However, the great distance from the registered region (the oral cavity) prevents the use of such intraoral templates for operations in the lateral skull base area [25].…”
Section: Discussionmentioning
confidence: 99%
“…The splint can be reversibly fixed to the maxillary dentition, and no invasively applied markers are needed. For intraoral interventions, such as the navigated placement of dental implants, the use of dental splint registration has already proven its applicability [16,17]. However, standard dental registration splints are not suitable for IGS of the lateral skull base as the considerable distance between the registration area (the oral cavity) and surgical area results in a high target registration error [4,5,18].…”
Section: Introductionmentioning
confidence: 99%
“…This integrates anatomical, biomechanical and esthetic effects. Surgeries with the use of the direct navigation technique facilitate precise implant positioning at the angle of future prosthetic reconstruction, which creates favourable conditions for full accommodation of the reconstruction, and not for the adaptation of the future prosthetic reconstruction to the implant position [15][16][17]. A navigation technique allows the operator to achieve full spatial orientation at every moment of the surgery and does not require surgical templates, which is known as a blind preparation through faucets in stereo-lithographic templates [18].…”
Section: Discussionmentioning
confidence: 99%